DUOLINGO APPLICATION EFFECTIVENESS: IMPROVING ENGLISH LISTENING SKILLS AMONG STUDENTS OF ENGLISH EDUCATION DEPARTMENT - Nabila, Putri; Muhammad Hifdil Islam; Nina Agus Hariati (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Listening skills are one of the key competencies in English language learning and are crucial to master in the era of globalization. Language learning applications such as Duolingo offer interactive learning methods that have the potential to enhance students' listening abilities, particularly in dealing with variations in accents and speech speed. This study aims to explore the effectiveness of using Duolingo in improving the listening skills of students in the English Education department at Zainul Hasan Genggong Islamic University. The method used is a qualitative case study with data collection techniques including participatory observation, semi-structured interviews, and documentation. The findings indicate that regular use of Duolingo can improve students' sensitivity to pronunciation, recognition of similar-sounding words, and comprehension of varying speech speeds. However, the limited range of accents available in the application poses a significant challenge, leading students to express the need for more diverse features and content. Overall, Duolingo has proven to be an effective technology-based language learning tool that supports independent learning and active engagement, although further innovation is needed to meet the demands of complex global communication. Keywords: Duolingo, listening, accents, speech speed, English language learning